2003
DOI: 10.1037/h0087415
|View full text |Cite
|
Sign up to set email alerts
|

Guidance of eye movements during conjunctive visual search: The distractor-ratio effect.

Abstract: The distractor-ratio effect refers to the finding that search performance in a conjunctive visual search task depends on the relative frequency of two types or subsets of distractors when the total number of items in a display is fixed. Previously, Shen, Reingold, and Pomplun (2000) examined participants' patterns of eye movements in a distractor-ratio paradigm and demonstrated that on any given trial saccadic endpoints were biased towards the smaller subset of distractors and participants flexibly switched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 58 publications
3
17
1
Order By: Relevance
“…Our results provide evidence that the visual search performance of monkeys is shaped by the proportion of distractors that share a feature with the target (especially color in this study) in a manner analogous to what has been observed in humans (Bacon and Egeth 1997;Egeth et al 1984;Kaptein et al 1995;Poisson and Wilkinson 1992;Shen et al 2000Shen et al , 2003Sobel and Cave 2002;Zohary and Hochstein 1989). This global context effect cannot, however, be entirely related to that observed when the number of distractors was manipulated: although the number of same-color distractors increased within the fixed-size display in the former task, the proportion of same-color distractors did not vary in the latter task.…”
Section: Influence Of Display Composition On Target Discriminabilitysupporting
confidence: 77%
See 1 more Smart Citation
“…Our results provide evidence that the visual search performance of monkeys is shaped by the proportion of distractors that share a feature with the target (especially color in this study) in a manner analogous to what has been observed in humans (Bacon and Egeth 1997;Egeth et al 1984;Kaptein et al 1995;Poisson and Wilkinson 1992;Shen et al 2000Shen et al , 2003Sobel and Cave 2002;Zohary and Hochstein 1989). This global context effect cannot, however, be entirely related to that observed when the number of distractors was manipulated: although the number of same-color distractors increased within the fixed-size display in the former task, the proportion of same-color distractors did not vary in the latter task.…”
Section: Influence Of Display Composition On Target Discriminabilitysupporting
confidence: 77%
“…Generally, both monkeys and humans bias their search by visiting distractors sharing one particular feature with the target (Bichot and Schall 1999;Buracas and Albright 1999;Motter and Belky 1998b;Shen et al 2003; see also Bolster and Pribram 1993;Zohary and Hochstein 1989), and they rarely fixate distractors that share no feature with the target (Bichot and Schall 1999;Findlay 1997). These studies suggest that different distractors have different values, and we wished to determine whether the variability in conjunction search performance could be accounted for by the exact arrangement of the stimuli in a search display.…”
Section: Introductionmentioning
confidence: 99%
“…The CVS task used in this study was based on similar tasks described in the neuropsychological and cognitive science literature (Kristjansson et al. ; Shen and Reingold ; Muggleton et al. ; Saevarsson et al.…”
Section: Methodsmentioning
confidence: 99%
“…The CVS task used in this study was based on similar tasks described in the neuropsychological and cognitive science literature (Kristjansson et al 2002;Shen and Reingold 2003;Muggleton et al 2008;Saevarsson et al 2008). The task was implemented in a block design paradigm consisting of two repetitions of an 8-sec rest stimulus followed by two repetitions of an 8-sec task stimulus.…”
Section: Taskmentioning
confidence: 99%
“…For instance, if we are searching for a bright yellow car in a crowded parking lot, similarly bright cars will preferentially attract our eye movements (Pomplun, 2006). When we perform conjunctive visual search, i.e., search for a target that is defined by a pair of properties (e.g., being both round and red), fixations cluster preferentially on items belonging to the less frequent property in the display (Shen et al, 2003). This illustrates the remarkable sensitivity of our eye movement system to the relative informativeness of different stimulus features during search.…”
Section: Background Information On Eye Movementsmentioning
confidence: 99%